Tamarind Seed Xyloglucans Promote Proliferation and Migration of Human Skin Cells through Internalization via Stimulation of Proproliferative Signal Transduction Pathways - W. Nie; A. M. Deters (Dermatology Research and Practice)
Xyloglucans (XGs) of Tamarindus indica L. Fabaceae are used as drug vehicles or as ingredients of cosmetics. Two xyloglucans were extracted from T. indica seed with cold water (TSw) and copper complex precipitation (TSc). Both were analyzed in regard to composition and influence on cell viability, proliferation, cell cycle progression, migration, MAPK phosphorylation, and gene expression of human skin keratinocytes (NHEK and HaCaT) and fibroblasts (NHDF) in vitro. TSw and TSc differed in molecular weight, rhamnose content, and ratios of xylose, arabinose, galactose, and glucose. Both XGs improved keratinocytes and fibroblast proliferation, promoted the cell cycle, and stimulated migration and intracellular enzyme activity of NHDF after endosomal uptake. Only TSw significantly enhanced HaCaT migration and extracellular enzyme activity of NHDF and HaCaT. TSw and TSc predominantly enhanced the phosphorylation of molecules that referred to Erk signaling in NHEK. In NHDF parts of the integrin signaling and SAPK/JNK pathway were affected. Independent of cell type TSw marginally regulated the expression of genes, which referred to membrane proteins, cytoskeleton, cytokine signaling, and ECM as well as to processes of metabolism and transcription. Results show that T. indica xyloglucans promote skin regeneration by a direct influence on cell proliferation and migration.